Assessing the Impact of Inflation on Household Consumption in Kisoro District: A Case Study of Ny Akabande Subcounty - Nzabanita, Alikanjero (Kabale University, 2022)
A Research Report Submitted to the Faculty of Education in Partial Fulfillment of the Requirement for a Ward of Bachelor of Arts Degree in Education of Kabale University